The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1007/s42770-021-00538-8
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and genotypic characterization of mcr-1-positive multidrug-resistant Escherichia coli ST93, ST117, ST156, ST10, and ST744 isolated from poultry in Poland

Abstract: Background A plasmid-mediated mechanism of bacterial resistance to polymyxin is a serious threat to public health worldwide. The present study aimed to determine the occurrence of plasmid-mediated colistin resistance genes and to conduct the molecular characterization of mcr-positive Escherichia coli strains isolated from Polish poultry. Methods In this study, 318 E. coli strains were characterized by the prevalence of mcr1–mcr5 genes, antimicrobial suscep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 69 publications
0
14
0
Order By: Relevance
“…A total of one of the mcr-1-positive isolates had a mutation in the chromosomal pmrB gene, further indicating that chromosomal and plasmid-mediated mechanisms simultaneously mediate COL resistance in E. coli strains of avian origin. There were 29 additional resistance genes (including ESBL, AmpC, and PMQR genes) in the mcr-1harbouring isolates, which were extensively diverse belonging to 50 STs (Zając et al, 2019;Cwiek et al, 2021) (Table 2), including HiR pandemic ExPEC clones ST167, ST38, ST117, ST58, ST69, ST88, ST10 and ST410 (Manges et al, 2019). This diversity proves that various plasmids resulted in a diverse range of clones carrying mcr-1 and genes coding against last-resort antimicrobials in Eastern Europe.…”
Section: -Eastern Europementioning
confidence: 89%
See 1 more Smart Citation
“…A total of one of the mcr-1-positive isolates had a mutation in the chromosomal pmrB gene, further indicating that chromosomal and plasmid-mediated mechanisms simultaneously mediate COL resistance in E. coli strains of avian origin. There were 29 additional resistance genes (including ESBL, AmpC, and PMQR genes) in the mcr-1harbouring isolates, which were extensively diverse belonging to 50 STs (Zając et al, 2019;Cwiek et al, 2021) (Table 2), including HiR pandemic ExPEC clones ST167, ST38, ST117, ST58, ST69, ST88, ST10 and ST410 (Manges et al, 2019). This diversity proves that various plasmids resulted in a diverse range of clones carrying mcr-1 and genes coding against last-resort antimicrobials in Eastern Europe.…”
Section: -Eastern Europementioning
confidence: 89%
“…The poultry industry in Eastern Europe has been reported to be a reservoir for MGHB (Karpíšková et al, 2017;Zając et al, 2019;Gelbíčová et al, 2019;Gelbicova et al, 2020, Cwiek et al, 2021. In Poland, 97 isolates carrying mcr-1.1 on diverse plasmids (IncX4, IncFI, IncHI2, IncQ1, TrfA, IncB/O/K/Z, and many others) were detected among 128 faecal COL-resistant E. coli (62.5%) recovered from poultry birds during 2011-2020 (Zając et al, 2019;Cwiek et al, 2021), suggesting that diverse promiscuous plasmids evolved mcr-1 in Poland since at least in 2011. There was an increase in mcr-1-carrying strains from 1.1% in 2011 to 11.6% in 2016, suggesting possible increasing use of COL in breeder farms in countries where day-old chicks are imported into Poland (Zając et al, 2019).…”
Section: -Eastern Europementioning
confidence: 99%
“…The novel serotype O128: H4 E. coli harboring astA was identified in the mcr-1 -positive E. coli EC21Z-14 belonging to ST117. The E.coli ST117 was an emerging foodborne zoonotic pathogen that has been isolated from the poultry, meat, human, and sea ecosystem [ 42 , 43 , 44 , 45 ]. A recent study showed that the ST117 strains isolated from different hosts had higher genetic similarity, suggesting that ST117 could transfer among different hosts [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with our results, since all the ST117 strains associated with the phylogroup F and carrying the bla CTX-M1 , bla CTX-M14 and bla SHV-12 genes have been isolated from chicken samples, in a similar way to that described by Ben Said et al [ 44 ]. ST117 is a potential zoonotic that poses a risk of extra-intestinal infections in humans [ 53 ], therefore surveillance of these strains raises concerns [ 54 ]. However, there is a lack of understanding of virulence traits, antimicrobial resistance patterns, and genomic evolution [ 55 ].…”
Section: Discussionmentioning
confidence: 99%